Face recognition by statistical regularization and dimensionality reduction - Ong, Alan Kuan Hai. (2013)
This report presents the concepts of both Principal Component Analysis and Eigenfeature Regularization and Extraction in a face recognition system. Details of the theory and experiments done on the FERET database using these approaches would be manifested in the report. This report also shows the platform used to carry out the experiments in order to compare the results with the theoretical ones.